The Discursive Regularities - Webb, David (Foucault's Archaeology, 2012)
THE UNITIES OF DISCOURSEIn this first chapter Foucault sets out a series of methodological decisions that inform the analyses to come, outlining his conception of discourse and the idea of the statement that will be central to much of what follows. The unities to which the title of the chapter refers are those around which historical studies were, and still are, commonly based, and which in Foucault's view have been accepted at the cost of reinforcing the constraints from which thinking in modernity has struggled to escape. Archaeology, it is intended, will break them down to reveal their construction and transformation, exposing to view a level of events that had previously been concealed behind a façade of ready-made concepts, subjects, objects and assumptions about the nature of change.The chapter begins with a list of concepts that Foucault proposes to use, or whose use he will analyse: discontinuity, rupture, threshold, limit, series and transformation. With the exception of ‘rupture’, all of these terms are derived from mathematics and were, at the time Foucault was writing, most rigorously defined there. Even the term ‘rupture’, apparently the odd one out, is associated with Bachelard's philosophy of science (where it designates the discontinuity between science and the forms of understanding that precede it), and so can also be traced back to the same neighbourhood.